Persepsi Umat Buddha Terhadap Penyembelihan Hewan Pada Tradisi Aruh Adat Baharin Kecamatan Halongudul - Luhita Luhita (STABN Sriwjaya, 2023)
The problem studied in this research is the perception of Buddhists towards animal slaughter in Halong sub-district, where this research has never been carried out by students of STABN Sriwijaya Tanggerang Banten. The research method used in this research is descriptive qualitative research method. Data collection techniques used interview, observation and documentation methods. The results of this research show that the majority of Buddhists in Halong District are in a dilemma. On the one hand, the implementation of the Baharin Traditional Aruh ceremony involves the slaughter of sacrificial animals which clearly violates Buddhist Pancasila. On the other hand, Buddhists in Halong do not dare to abolish the Baharin Traditional Aruh ceremony for fear of disaster. The solution to this dilemma is to continue carrying out ceremonies involving the slaughter of sacrificial animals on the condition that Buddhists must perform other greater virtues and take care not to violate many other precepts of the Buddhist Pancasila